The Effect of Adjustment of Endotracheal Tube Cuff Pressure during Scarless Remote Access Endoscopic and Robotic Thyroidectomy on Laryngo-Pharyngeal Complications: Prospective Randomized and Controlled Trial - Koo, Chang-Hoon (J Clin Med, 2019)
Scarless remote access endoscopic and robotic thyroidectomy has been recently performed as a safe and feasible method. However, little is known about the laryngo-pharyngeal complications after surgery and the effect of adjusting the endotracheal tube cuff pressure during surgery on laryngo-pharyngeal complications. Patients were randomized into two groups: the control group (n = 52) and adjusted group (n = 52). The initial cuff pressure was set to 25 mmHg and then monitored without adjustment (control group) or with adjustment at approximately 25 mmHg (adjusted group) throughout surgery. The incidences and severity of postoperative sore throat (POST), hoarseness, dysphagia, and cough were recorded at 1, 6, 24, and 48 h after surgery. Cuff pressures of the control group changed significantly over time and were higher than those of the adjusted group. The incidence of POST was lower in the adjusted group at 24 h postoperatively (p = 0.035), and there was a significant difference in the severity of POST at 6 and 24 h postoperatively between the two groups. There were no differences in the incidence of hoarseness, dysphagia, and cough between the two groups, except dysphagia and cough at 6 h postoperatively. Therefore, intraoperative monitoring and adjustment of the cuff pressure can reduce the incidence of laryngo-pharyngeal complications.